Educating Seniors Against Dementia Through Knitting Skills and Crossgenerational Collaboration - Andhini Winariyanti; Deta Anggraini; Tatik Yuniarti (Interdisciplinary Social Studies, 2026)
The Rajut Asa Program is a community-based empowerment program aimed at improving the psychosocial well-being and cognitive health of the elderly while simultaneously engaging youth through intergenerational collaboration. Implemented in RW 01, Bidara Cina Village, East Jakarta, the program involved 16 elderly women and 4 Karang Taruna youth members. This initiative integrates three main components: craft-based therapy, intergenerational interaction, and local economic empowerment. The program's effectiveness was evaluated using a mixed-methods approach that combined pretest-posttest quantitative assessments with qualitative observations. The results showed significant improvements in the elderly participants' self-confidence, social support, and cognitive engagement, with an effect size of . The youth also demonstrated substantial increases in intergenerational empathy and leadership readiness, with an effect size of . Overall, the program effectively enhanced participants' cognitive activity, social involvement, and fine motor skills while laying the foundation for a sustainable creative economy model. This study contributes a novel holistic integration of therapeutic intervention, intergenerational collaboration, and creative economy development within a single community program. The findings hold significant public health policy relevance by demonstrating that low-cost, community-asset-based interventions can effectively address the escalating dementia crisis in resource-constrained settings. They offer scalable alternatives to expensive clinical interventions and contribute evidence for age-friendly community development strategies aligned with WHO guidelines on dementia risk reduction. This low-cost, asset-based program design—utilizing local skills and community assets—can be replicated in similar urban communities to promote elderly well-being and intergenerational cohesion.